2018
DOI: 10.12659/msm.909365
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol on the Expression of G-Protein Coupled Estrogen Receptor (GPER/GPR30) Mitophagy, and the PI3K/Akt Signaling Pathway in ATDC5 Chondrocytes In Vitro

Abstract: BackgroundOsteoarthritis is a progressive inflammatory joint disease resulting in damage to articular cartilage. G-protein coupled estrogen receptor (GPER/GPR30) activates cell signaling in response to 17β-estradiol, which can be blocked by the GPR30 agonist, G15, an analog of G-1. The aims of this study were to investigate the effects of 17β-estradiol on the expression of G-protein coupled estrogen receptor (GPER/GPR30) on mitophagy and the PI3K/Akt signaling pathway in ATDC5 chondrocytes in vitro.Material/Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 64 publications
(64 reference statements)
2
40
0
Order By: Relevance
“…It is also important to note that chondrocytes are affected by many pathways, including the PI3K/Akt/Bcl pathway, which is involved in chondrocyte metabolism, growth, proliferation, survival, transcription, and protein synthesis . We supplemented the Western blot of the key protein PI3K, Akt, Bcl‐2 in this pathway, and the results are shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that chondrocytes are affected by many pathways, including the PI3K/Akt/Bcl pathway, which is involved in chondrocyte metabolism, growth, proliferation, survival, transcription, and protein synthesis . We supplemented the Western blot of the key protein PI3K, Akt, Bcl‐2 in this pathway, and the results are shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that knockout of PHF23 prevent the chondrocytes apoptosis against IL-1βinduced OA by increasing autophagy, mitophagy, collagen II expression and reducing the OA-related proteins, which might make PHF23 a possible therapeutic target for OA [142]. Fan et al [143] demonstrated that 17β-estradiol, a steroid hormone, inhibited mitophagy by activating the PI3K/AKT/ mTOR signaling pathway via the G-protein coupled estrogen receptor to exert protective effect on chondrocytes in OA. In addition, Blanco et al [144] indicated their hypothetic view on the key role of AMPK-SIRT-Parkin in regulating mitochondrial function and defensing against excessive ROS in the chondrocytes of OA ( Figure 6A).…”
Section: Oamentioning
confidence: 99%
“…Nonetheless and considering that 17β-E 2 was shown to induce GPR30 expression in ATDC5 mouse chondrogenic cells (Fan et al, 2018), it is also possible that GPR30 is only stably expressed…”
Section: Discussionmentioning
confidence: 99%